Implementasi Etika Bisnis Islam dalam Meningkatkan Loyalitas Pelanggan Pemasok pada Umkm Pengepul Cabe Jawa Barokah Desa Jambearum Kecamatan Puger Kabupaten Jember - Miftahul Hasanah; Dhofir Catur Bashori; Rohmad Aldi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the Islamic business ethics implemented by MSMEs collecting Javanese Barokah chilies in Jambearum Village, Puger District, Jember Regency and the impact of implementing Islamic business ethics in increasing supplier customer loyalty to MSMEs collecting Javanese Barokah chilies, Jambearum Village, Puger District, Jember Regency. To identify problems and answer research problems, this research uses qualitative research with a case study approach and purposive subject determination techniques. The data collection techniques for this research use active participatory observation, semistructured interviews and documentation. The results of the research concluded that: (1) MSME actors collecting Barokah Javanese chilies in Jambearum Village, Puger District, Jember Regency have implemented the 5 principles of Islamic business ethics in running their business, including: Unity Principle, Equilibrium Principle, Free Will Principle ( Free Will), Principle of Responsibility (Responsibility), Principle of Truth: Virtue and Honesty. (2) The impact of implementing Islamic business ethics in increasing supplier customer loyalty in MSME Java Barokah Chili Collectors, Jambearum Village, Puger District, Jember Regency, has seen customer loyalty expressed by supplier customers with the realization of service quality, customer satisfaction and perceived customer value.